An overview of applications of mucoadhesive buccal film in Oral Medicine - Gupta, Pankaj (Journal of Orofacial Research, 2020)
The mucosal covering of the oral cavity connects the external environment to interior of the body. This mucosal barrier, however subjected to different types of pathologies which require local treatment such as gingivitis, periodontal disease, oral candidiasis, herpes and aphthous ulcers. Amongst the diverse routes of drug delivery, oral route is the most desirable and is convenient to both clinician and patient. Since oral administration of drugs have certain limitations such as drugs undergoing first pass metabolism and enzymatic degradation within the gastrointestinal tract, limits oral bioavailability of drugs. For this reason, several buccal formulations like gels, mucoadhesive tablets , patches and buccal films have been developed that allow direct contact with the oral mucosa and provide a prolonged release of the drug, reducing the need for frequent drug doses.